Understanding how consumer education impacts shoppers over time: A longitudinal field study of unit price usage. (September 2016) - Weeks, Clinton S.; Mortimer, Gary; Page, Lionel
Abstract: There remains a lack of empirical evidence for what constitutes effective consumer education around unit pricing in grocery stores, despite researchers continually highlighting the importance of such education. Much of the early work on unit pricing describes self-report estimates of usage, or results of simulated shopping studies which can lack external validity. The current research reports one of the first longitudinal field experiments to examine the impact of consumer education on unit price usage over time, and is based on shoppers' actual grocery spending. Shoppers receiving consumer education displayed progressively higher levels of savings across the first six weeks of the study to a peak of about 17–18%, declining to around 11–13% by the end of the study. Savings were achieved by shoppers from all income levels, and increased with the provision of personalized comparative feedback. The study offers theoretical insights and important practical implications for retailers and policy makers.